2014
DOI: 10.1259/dmfr.20130366
|View full text |Cite
|
Sign up to set email alerts
|

Digital orthopantomograms in osteoporosis detection: mandibular density and mandibular radiographic indices as skeletal BMD predictors

Abstract: Objectives: To determine the correlation of skeletal bone mineral density (BMD) with mandibular density and mandibular radiographic indices estimated on digital panoramic radiographs. Methods: Study comprised 112 female subjects older than 45 years. Digital panoramic radiographs were taken, and patients were referred to densitometric measuring (dual energy X-ray absorptiometry) of BMD in the hip bones and lumbar spine regions (L1-L4). On the radiographs, mandibular bone density was estimated and the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
(39 reference statements)
6
26
0
3
Order By: Relevance
“…Passos et al concluded that women with osteoporosis or osteopenia have two times higher incidence of periodontal disease. Supporting evidence is correlation of mandibular bone density and skeletal BMD, previously reported result found in our study sample . Similar finding had Vishwanath et al who analysed correlation of mandibular bone density and os calcis.…”
Section: Discussionsupporting
confidence: 92%
“…Passos et al concluded that women with osteoporosis or osteopenia have two times higher incidence of periodontal disease. Supporting evidence is correlation of mandibular bone density and skeletal BMD, previously reported result found in our study sample . Similar finding had Vishwanath et al who analysed correlation of mandibular bone density and os calcis.…”
Section: Discussionsupporting
confidence: 92%
“…Mandibular bone quality can be assessed using intraoral radiographs, panoramic radiographs, CBCT, quantitative and dual-energy X-ray absorptiometry. [4][5][6][7][8] There are several radiomorphometric indices that use measurements in panoramic radiographs, which have been suggested as possible indicators of decreased value of bone mineral density. [7][8][9] It was shown that CBCT can also be used to determine mandibular indexes in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] There are several radiomorphometric indices that use measurements in panoramic radiographs, which have been suggested as possible indicators of decreased value of bone mineral density. [7][8][9] It was shown that CBCT can also be used to determine mandibular indexes in several studies. 5,6,10,11 Panoramic radiography cannot illustrate the buccolingual width and also distorts the images.…”
Section: Introductionmentioning
confidence: 99%
“…(American Dental Association Council on Scientific Affairs, 2006) y se reconoce que su sensibilidad y especificidad varían de acuerdo a cada hallazgo, pero es evidente que es un examen valido en estudios epidemiológicos, por ser de bajo costo y seguro (Hugoson et al, 2005;Choi et al, 2011). Con muestras importantes de radiografías se ha podido detectar la prevalencia de dientes incluidos, asimetrías mandibulares, anomalías dentales tanto de número (Fardi et al, 2011) como de forma (Shokri et al, 2014), variaciones anatómicas, quistes y tumores de los maxilares, y alteraciones de crecimiento y desarrollo (Bernaerts et al, 2006;Espinal Botero et al, 2009;Schmuckli et al, 2010). Su utilidad en la identificación postmortem y determinación de la edad de un individuo así como patologías sistémicas que se asocian con hallazgos en las estructuras anatómicas maxilofaciales, como ateromas carotideos (Ngamsom et al, 2015), calcificaciones pulpares asociadas a eventos cardiovasculares (Khojastepour et al, 2013) y cambios en el índice mandibular en pacientes con osteoporosis (Savic Pavicin et al, 2014) son algunos de los ejemplos de la utilidad de la radiografía panorámica.…”
Section: Introductionunclassified